Comparison of the Effectiveness of Emotional Intelligence Training and Spiritual Intelligence Training on Executive Functions in Students with Learning Disorders - Ghasemi Bakhtiyari, Fateme; Naderi, Habibollah; Donyavi, Reza (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted with the aim of comparing the effectiveness of emotional intelligence training and spiritual intelligence training on executive functions in students with learning disorders. The present research was a quasi-experimental study with a pretest–posttest and follow-up design including a control group. The statistical population consisted of all students with learning disorders in Pishva, Varamin, who had referred to specialized learning disorder centers in Pishva, Varamin, in 2025; the research sample included 45 participants who were selected using convenience sampling and randomly assigned to two experimental groups and one control group, each consisting of 15 participants. The Nejati Cognitive Abilities Questionnaire (Nejati, 2013) was used for data collection. Multivariate analysis of variance (MANOVA) with repeated measures was used to analyze the data using SPSS software. The results indicated that there was a statistically significant difference between the effectiveness of emotional intelligence training and spiritual intelligence training on memory and sustained attention in students with learning disorders (p < .05). Emotional intelligence training resulted in significant improvements in memory, inhibitory control, decision-making, planning, and sustained attention scores (p < .05). Spiritual intelligence training resulted in significant improvements in memory and planning scores (p < .05). However, spiritual intelligence training did not have a statistically significant effect on inhibitory control, decision-making, or sustained attention scores (p > .05). Therefore, emotional intelligence training and spiritual intelligence training can be considered effective methods for improving executive functions in students with learning disorders.